Employees' Understanding of Service-Oriented Strategy: A Case of Business Services in Indonesia - Putra, Ida Bagus Udayana; Amerta, I Made Suniasta (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
Organizational culture refers to the underlying beliefs, assumptions, values, and interaction styles contributing to the distinctive social and psychological environment. The study was measured statistically with approximately 200 participants in Indonesia. The service-oriented strategy had a significant good and direct influence on business services, while the greater service-oriented strategy had an extra influence on the respondents' organizational readiness and knowledge exchange. Through their business services, service-oriented firms seek to delight customers, produce and deliver customer value in the marketplace, and enhance their company's performance and profitability. In order to meet the ever-increasing demands of investors, employees, and consumers, business organizations are continuously under pressure to assess and enhance their performance in competitive markets. As a result, businesses partition their organization and related business services into smaller, self-sufficient company components that can interact to optimize efficiency. In order to be capable of providing excellent services, business services must clearly adhere to business-oriented strategies. Keywords : business strategy, business process, governance, business information system